Webtoon Design with Alternative Universe Theme - Humaira Muchsin, Aulia; Septian Rachman, Vicky (TOPAZART, 2024)
With the development of technology, comics can be accessed anywhere and anytime with various devices and sites. Comic artists no longer have to rely on publishers to publish their work. Many companies are also updating their products from changing their brand look to providing the new product to a new platform. Webtoon os an online comic platform that has become popular with its application and website. Even though it looks like it wont make any profit, Webtoon has become a platform for novice and advanced comic artist to earn income from becoming a brand ambassador. On the Webtoon platform there are many comic genres, one of the popular genres is the alternative universe where the new original characters enters a world that already exist such as the world of a film or comic. This design aims to explore characters and develop alternative universe genres in webtoon comics that are interesting for readers on online platforms.